The inverse electro-oculogram. Issue 6 (June 1982) - Doft, B H; Burns, S A; Elsner, A
Abstract : An electro-oculogram ratio of less than one was found to be caused by limited ocular excursions under photopic conditions in a patient with a rod-cone dystrophy. Because this inverse electro-oculogram ratio was not caused by a decrease in standing potential under photopic conditions, it should be considered an artefact.